A ROS/Gazebo-based framework for simulation and control of on-orbit robotic systems - Ramón, José Luis; Pomares, Jorge; Felicetti, Leonard (International Astronautical Federation (IAF), 2022)
The use of simulation tools such as ROS/Gazebo is currently common practice for testing and developing control algorithms for typical ground-based robotic systems but still is not commonly accepted within the space community. Numerous studies in this field use ad-hoc built, but not standardized, not open-source, and, sometimes, not verified tools that complicate, rather than promote, the development and realization of versatile robotic systems and algorithms for space robotics. This paper proposes an open-source solution for space robotics simulations called OnOrbitROS. This paper presents a description of the architecture, the different software modules, and the simulation possibilities of OnOrbitROS. It shows the key features of the developed tool, with a particular focus on the customization of the simulations and eventual possibilities of further expansion of the tool. In order to show these capabilities, a computed torque-based controller for the guidance of a free-floating manipulator is proposed and simulated using the ROS/Gazebo-based framework described in the paper.
Keywords: space robot; humanoid robot; robot control; ROS